The Development of Human Health in the Crusade Era in Europe - Muhammad Alfarisi; Niken Yuliana (Yayasan Yusda Edu Indonesia, 2026)
The Crusades were a series of prolonged conflicts between the Islamic world and Christianity that took place from the late eleventh century to the late thirteenth century. These events were not solely triggered by religious factors but were also influenced by political, economic, and social interests from both sides. This article aims to examine the background of the Crusades, their main periods (the First, Second, and Third Crusades), and their impacts on the Islamic world, Europe, and global civilization in general. The research employs a historical method with a qualitative approach through library research. The findings indicate that the Crusades had complex consequences, ranging from military and social losses in the Islamic world to economic, political, and intellectual advancements in Europe. Moreover, the Crusades became a significant turning point in the process of cultural and scientific exchange between the East and the West, which has continued to influence the modern world.